Analisis Prosedur Klaim Asuransi Jaminan Kesehatan Nasional Pasien Rawat Inap RSUD Lembang - Hafni Zahara; Dian Amalia Rahmi; Ai Susi Susanti (Jurnal Health Sains, 2021)
Implementation of the National Health Insurance Claim Procedure at the Lembang Hospital in the Implementation of the National Health Insurance Claim Procedure is guided by the cooperation agreement between Lembang Hospital and the Cimahi branch of BPJS. Based on the results of interviews, officers still found obstacles including incomplete medical support data, administrative requirements that were still lacking, such as patients who did not carry ID cards, family cards, resulting in incomplete filling of patient identity files, inactive BPJS cards, and loss of letters. Referral causes the claim procedure to be hampered. The purpose of this study was to determine the Procedure for Claiming National Health Insurance for Inpatients at Lembang Hospital. The method used is using the interview and observation methods. The type of research used in this study uses a descriptive method with a qualitative approach. Assembling, coding and data entry officers for INA CBGs act as subjects, while the object of this research is the JKN Claim Procedure for inpatients at Lembang Hospital. the process of collecting data using interviews and observation. The data processing technique used in this research is colleting, editing, and presenting data.